Target Hafalan sebagai Motivasi Belajar dalam Membentuk Karakter di Lingkungan Pesantren - Muhammad Anas Ma`arif; Salamatu Rochmah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2018)
Education is a place to create a cadre of people who excel cognitive, affective, psychomotor and spiritual. To achieve this goal, it is necessary to have motivation to be able to carry out all educational goals. Building learning motivation within the pesantren environment, including one of which is targeted. Memory memorization that is carried out consistently can be a learning motivation for students. With the growing learning motivation of students, their goals can be easily achieved, including the goals of Islamic education. And one of the goals of Islamic education is to form noble character or character formation. the purpose of this paper is to explain and analyze memorized targets to build students' motivation to form characters in the pesantren environment. This study uses the study of library research, which collects books, journals and research results that are relevant to the theme. memorized targets are adjusted to the age conditions of santri with habituation, exemplary, reward and punishment strategies. the character is formed by refracting to carry out memorization and motivation to carry out with awareness.